2014
DOI: 10.1016/j.cell.2014.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Tetrameric c-di-GMP Mediates Effective Transcription Factor Dimerization to Control Streptomyces Development

Abstract: SummaryThe cyclic dinucleotide c-di-GMP is a signaling molecule with diverse functions in cellular physiology. Here, we report that c-di-GMP can assemble into a tetramer that mediates the effective dimerization of a transcription factor, BldD, which controls the progression of multicellular differentiation in sporulating actinomycete bacteria. BldD represses expression of sporulation genes during vegetative growth in a manner that depends on c-di-GMP-mediated dimerization. Structural and biochemical analyses s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
308
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(322 citation statements)
references
References 59 publications
10
308
0
2
Order By: Relevance
“…Binding of tetrameric CDG to BldD brings together the DNA binding domains of the BldD dimer, thus enabling the protein to bind to its target sites (224). An example of metabolic control is presented by the pleiotropic nutrient sensory regulator DasR, which is essential for development and pleiotropically represses antibiotic production (see below).…”
Section: The Streptomyces Life Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…Binding of tetrameric CDG to BldD brings together the DNA binding domains of the BldD dimer, thus enabling the protein to bind to its target sites (224). An example of metabolic control is presented by the pleiotropic nutrient sensory regulator DasR, which is essential for development and pleiotropically represses antibiotic production (see below).…”
Section: The Streptomyces Life Cyclementioning
confidence: 99%
“…Recently, it was elegantly shown by the group of Mark Buttner that the activity of BldD, which represses many developmental genes during vegetative growth, is controlled posttranslationally by the signaling molecule cyclic-di-GMP (CDG) (224). Binding of tetrameric CDG to BldD brings together the DNA binding domains of the BldD dimer, thus enabling the protein to bind to its target sites (224).…”
Section: The Streptomyces Life Cyclementioning
confidence: 99%
“…Although a diverse set of DNA-binding proteins have been experimentally identified as c-di-GMP-binding proteins, MrkH is thus far the only DNA-binding protein predicted to harbor a PilZ domain (18,(27)(28)(29)(30)(31). Data indicate that c-di-GMP binding to MrkH stimulates its ability to bind a consensus DNA sequence called the MrkH box, TATCAA, located upstream of the −35 site in the mrkABCDF promoter (6,8).…”
mentioning
confidence: 99%
“…In addition to biofilm formation, processes regulated by c-di-GMP include motility, virulence, and the cell cycle (15)(16)(17). Moreover, recent work has revealed that c-di-GMP serves as the switch that controls Streptomyces development and secondary metabolite production (18). Our understanding of the proteins and networks that drive c-di-GMP-dependent processes are, however, still in its infancy, largely because of the difficulty in identifying c-di-GMP-binding motifs within effector proteins.…”
mentioning
confidence: 99%
“…By growing Streptomyces in a microfluidic device connected to a fluorescence widefield microscope (Figure 2), we are now able to monitor germination, vegetative growth and sporulation septation over a time period of up to 30 hr. This is greatly facilitated by the use of the new model organism Streptomyces venezuelae because it sporulates to near completion in submerged culture and thereby overcomes the limitation of the classical model species S. coelicolor, which sporulates only on solid media [16][17][18][19][20] . To help visualize vegetative growth and sporulation, we co-express fluorescently tagged versions of the cell polarity marker DivIVA and the key cell division protein FtsZ.…”
Section: Introductionmentioning
confidence: 99%